The coulombic sigma-hole model describes bonding in CX3I center dot center dot center dot Y- complexes completely - Clark, Timothy; Heßelmann, Andreas (Physical Chemistry Chemical Physics, 2018)
Contrary to recent reports, the sigma-hole interaction energies of complexes between the carbon tetrahalides CX3I (X = F, Cl, Br, I) and halide anions Y- (Y = F, Cl, Br, I) are described very well by the simple Coulombic sigma-hole concept if it is applied properly. There is no need to invoke charge transfer, which in any case is not uniquely distinguishable from polarization.